REFLEKSI 5 TAHUN PASKA ERUPSI GUNUNG MERAPI 2010: MENAKSIR KERUGIAN EKOLOGIS DI KAWASAN TAMAN NASIONAL GUNUNG MERAPI - Hero Marhaento; Asep N Kurnia (Department of Urban and Regional Planning, Diponegoro University, 2015)
Ecological loss assessment at the Mount Merapi National Park (MMNP) after Mount Merapi (MM) eruption in the year 2010 has not been done before. The present study aims to estimate the ecological loss at the MMNP after 2010 eruption based on Rapid Damage Appraisal Assessment. Three steps were executed: (1) identifying and mapping damages in the MMNP using remote sensing data, (2) collecting in-situ information through field assessment, (3) estimating ecological loss assessment using economic valuation approach. Two methods of economic valuation were used, namely the change in productivity (i.e. carbon stock loss) and replacement cost (i.e. land restoration cost). The results showed that approximately of 1,242 ha (19.37%) of MMNP area was heavily damaged, 1,208 ha (18.84%) was moderately damaged, and the rest was slightly damaged. The heavy damage and the moderate damage were occurred in the forest block of resort Pakem-Turi, Cangkringan, Srumbung, Dukun, Sawangan, Selo and Kemalang. The slight damage was occurred in the forest block of resort Musuk-Cepogo, Kemalang and Selo. The ecological loss was estimated in a total of 766 Billion Indonesian rupiah consist of 747.50 Billion Indonesian rupiah from carbon stock loss and 18.5 Billion Indonesian rupiah from land restoration cost. The total ecological loss was estimated approximately 38.3 Trillion Indonesian rupiah, which was a raw estimation and considered undervalued. © 2015 GJGP UNDIP. All rights reserved.